2022
DOI: 10.3389/fphar.2022.891069
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Autophagy and Innate Immunity: A Pivotal Role in Hepatic Fibrosis

Abstract: Liver fibrosis is a repair process of chronic liver injuries induced by toxic substances, pathogens, and inflammation, which exhibits a feature such as deposition of the extracellular matrix. The initiation and progression of liver fibrosis heavily relies on excessive activation of hepatic stellate cells (HSCs). The activated HSCs express different kinds of chemokine receptors to further promote matrix remodulation. The long-term progression of liver fibrosis will contribute to dysfunction of the liver and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…The vast majority of lymphocytes engulfed by phagocytosis in liver cells are CD8+ T cells and are mainly observed in the area of caspase-3-induced apoptosis [ 399 ]. NK cells are involved in liver fibrosis [ 400 ]. HSCs impair the killing effect of NK cells by TGFβ secretion [ 401 ].…”
Section: Implication Of Autophagy In the Commonalities Between Autoim...mentioning
confidence: 99%
“…The vast majority of lymphocytes engulfed by phagocytosis in liver cells are CD8+ T cells and are mainly observed in the area of caspase-3-induced apoptosis [ 399 ]. NK cells are involved in liver fibrosis [ 400 ]. HSCs impair the killing effect of NK cells by TGFβ secretion [ 401 ].…”
Section: Implication Of Autophagy In the Commonalities Between Autoim...mentioning
confidence: 99%
“…Liver fibrosis (HF) is an important link in the progression of chronic inflammation in the liver to cirrhosis and hepatocellular carcinoma, therefore, effective suppression of the inflammatory response is the key to the treatment of HF (Chen et al, 2022). Autophagy, an inflammationrelated defense mechanism in chronic liver disease, is considered a new target for the treatment of liver fibrosis (Chen et al, 2022). Liu et al…”
Section: Liver Fibrosismentioning
confidence: 99%
“…Liver fibrosis (HF) is an important link in the progression of chronic inflammation in the liver to cirrhosis and hepatocellular carcinoma, therefore, effective suppression of the inflammatory response is the key to the treatment of HF (Chen et al, 2022). Autophagy, an inflammation‐related defense mechanism in chronic liver disease, is considered a new target for the treatment of liver fibrosis (Chen et al, 2022). Liu et al showed that catalpol significantly inhibited the release of inflammatory cytokines by activating autophagy, thereby suppressing the inflammatory response and ultimately alleviating liver fibrosis (Liu et al, 2018).…”
Section: The Anti‐inflammatory Effects Of Catalpol In Various Diseasesmentioning
confidence: 99%
“…Studies indicate that an imbalance in the immune microenvironment of the liver is the main driver of liver fibrosis ( 12 ). Autophagy, which is regulated by a diverse array of immune cells, plays a role in managing the liver’s immune microenvironment ( 13 , 14 ). Analysis of immune cell infiltration provides insights into the distribution and quantity of immune cells within liver tissue.…”
Section: Introductionmentioning
confidence: 99%